2013
DOI: 10.1371/journal.pone.0075064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Tibeto-Burman Populations of Bangladesh: Evaluating the Gene Flow along the Sides of Bay-of-Bengal

Abstract: Human settlement and migrations along sides of Bay-of-Bengal have played a vital role in shaping the genetic landscape of Bangladesh, Eastern India and Southeast Asia. Bangladesh and Northeast India form the vital land bridge between the South and Southeast Asia. To reconstruct the population history of this region and to see whether this diverse region geographically acted as a corridor or barrier for human interaction between South Asia and Southeast Asia, we, for the first time analyzed high resolution unip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Demographic studies have documented crossovers between these two geographically close population groups (Gazi et al 2013), which could possibly be reflected in the findings of the present study, where we observed an incidence of 21.21 % of Inca bone in skulls of a population from Eastern India (Figs. 2, 3), which is significantly higher than the incidence reported from other regions of India, as well as most of the other population groups of the world (Singh et al 1979;Marathe et al 2010;Berry and Berry 1967).…”
Section: Discussionsupporting
confidence: 74%
“…Demographic studies have documented crossovers between these two geographically close population groups (Gazi et al 2013), which could possibly be reflected in the findings of the present study, where we observed an incidence of 21.21 % of Inca bone in skulls of a population from Eastern India (Figs. 2, 3), which is significantly higher than the incidence reported from other regions of India, as well as most of the other population groups of the world (Singh et al 1979;Marathe et al 2010;Berry and Berry 1967).…”
Section: Discussionsupporting
confidence: 74%
“…mtDNA control regions sequence of this population showed lower sequence diversity 0.8475 ± 0.0134, than the tribal Indian-specific diversity 0.989 (95% CI: 0.975, 0.969) indicating gene flow shares with East and Southeast Asian specific diversity than Indian diversity [19]. The random match probability is 8.09% with 43 substitutions.…”
Section: Haplogroup Structure and Most Common Haplotypesmentioning
confidence: 69%
“…In fact, a precise haplogroup classification is an issue of increasing importance when mtDNA analysis is applied to forensic casework. The distributions of mtDNA haplogroups in mainstream population of Bangladesh are less complex than those of the tribal populations of Chittagong Hill-Tracts [19] and West Bengal of India [20]. The low sequence diversity of mainstream Bangladeshi population indicated that this population are distinct than those of Thailand, Myanmar, and Northeast India.…”
Section: Discussionmentioning
confidence: 94%
“…1). All structure runs performed 40,000 iterations after a burn-in of 50,000, following the admixture model and sample group information method described elsewhere [5].…”
Section: Methodsmentioning
confidence: 99%
“…The populations of Bangladesh constitute mostly Bengali speakers (a branch of Indo-Aryan language), while the remaining are tribal groups affiliated with Dravidian, Indo-European, Austroasiatic and Tibeto-Burman language families [1][2][3]. The number of genetic studies of this region is very limited and mainly restricted to forensic markers for a few caste and tribal populations [4][5][6][7][8]. Several of the tribes are yet to be investigated and none of the study however, so far have analysed a large number of tribal and caste populations.…”
Section: Introductionmentioning
confidence: 99%